Invasive Mucormycosis with Lung Involvement in a Female Patient with Aplastic Anemia - Zh. V. Sheikh; I. E. Tyurin; A. I. Sinopal’nikov; A. V. Arablinskiy; T. D. Safonova; E. V. Fedyaeva; O. B. Murav’ev; S. N. Shvayko (Вестник рентгенологии и радиологии)
Mucormycosis is an infection caused by one of several types of mold. Invasive mucormycosis is the most aggressive, rapidly progressive fungal infection. The disease is characterized by high attributable mortality. The early and accurate diagnosis of invasive mucormycosis determines the choice of an adequate therapeutic policy, by improving the prognosis of the disease. The method of choice for diagnosing pulmonary mucormycosis is computed tomography that allows accurate determination of the location and extent of the lesion, the state of the lung parenchyma, and the presence of concomitant complications. The paper describes a clinical case of damage to the lung and skin in invasive mucormycosis in a 28-year-old woman with aplastic anemia. The case is of interest due to a larger number of immunocompromised patients, especially those susceptible to the disease.